Voting and winning: perceptions of electoral integrity in consolidating democracies. Issue 8 (17th November 2021) - Mochtak, Michal; Lesschaeve, Christophe; Glaurdić, Josip
ABSTRACT: How do voters in consolidating democracies see electoral integrity? How does election affect the change in perception of electoral integrity among these voters? What role does winning play in seeing an election as free and fair? Building on the theory of the winner-loser gap, we answer these questions using original two-wave panel surveys we conducted before and after three parliamentary elections in Southeast Europe in 2018 and 2020. The article focuses on changes of perception of electoral integrity as a function of satisfaction with the electoral results in contexts where the quality of elections has always been at the centre of political conflict. We specifically explore the socialization effect of elections in environments with notoriously low trust in political institutions and high electoral stakes. The article goes beyond the "sore loser" hypothesis and examines voters' both political preferences and personal characteristics potentially responsible for the change in perception of electoral integrity over the course of electoral cycle.